Preface - Papageorghiou, A (Elsevier, 2018)
Few subjects capture the imagination more than how humans grow and develop. The apparent biological simplicity of two cells coming together belies the enormously complex and highly regulated changes that will result in a fetus and newborn. The link between our physical development into what makes us who we are, with the behavioral, cognitive, and emotional changes we experience during our lifetime, are of course shaped by innumerable factors – our genes, our environment, education and cultural milieu. But it is also increasingly clear that our short “start in life” – just 280 or so days of intra-uterine existence - has a profound effect on our subsequent chances of healthy development.